Play for sick children : play specialists in hospitals and beyond - Hubbuck, Catherine (Jessica Kingsley, 2009)
This book offers an insight into the work of play specialists, examining the repercussions of being ill and receiving treatment experienced by children and their families. The author proposes that play should be a high priority for those working in hospitals and challenges other health professionals to recognise its value.